Leadership Succession and Psychological Readiness: The Role of Solitude and Psychodynamic Elements - Fauzan Fadli (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the influence of solitude as a psychodynamic competency on the succession readiness of emerging leaders in State-Owned Enterprises (SOEs) and other strategic organizations. Methodology: This study employed a quantitative approach using a cross-sectional survey. Data were collected from 187 emerging leaders and analyzed using descriptive statistics, reliability tests, and Pearson’s correlation analysis. Results: The findings indicate that all examined psychodynamic elements, namely anxiety management, emotional regulation, self-reflection, constructive narcissism, and authenticity, demonstrate significant positive correlations with succession readiness. Anxiety management emerged as the strongest predictor. Conclusions: This study confirms that solitude serves as a crucial integrative psychodynamic competency that significantly enhances an individual's psychological preparedness for leadership succession. Limitations: The main limitations include the cross-sectional design, which prevents the establishment of causality, and the potential for common method bias inherent in the self-reported data. The generalizability of the findings may also be limited by the relatively homogenous sample. Contributions: This research offers practical insights for organizational leaders and HR practitioners in developing effective succession plans. Theoretically, this study enriches the leadership development literature by empirically validating the link between psychodynamic competencies and succession preparedness.